Implementation of Work-Based Learning at Teaching Factory in Vocational Education - Yoto, Yoto; Marsono, Marsono (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Vocational education aims to prepare graduates to be work-ready. Vocational education institutions, as preparer and providers of skilled labor candidate, must be able to utilize their resources and network partnerships resources with outsiders effectively. One way to meet the objectives of vocational education is to apply work-based learning in teaching factories. Work-based learning is a Contextual teaching-learning (CTL) approach where the business world or industrial world provides a set of structured work-based learning experiences. While teaching factory is the development of the production unit, namely the implementation of industrial partnership systems in the existing production units at SMK. The implementation of work-based learning in teaching factories in vocational education is expected to be able to increase the competitiveness of graduates.